“Where will you be after one year and a half as a refugee?” – Refugees experiences and aspirations of social integration in Lisbon” - Mateus, S.; Santos, P. (The Universe(s) of Refugees: Rethinking Forced Migration, 2019)
Four years have passed since asylum applications in Europe reached their peak with a registered number of 1.3 million requests. Since then, there’s been a consistent remission of the influx. While numbers might contribute to political rhetorics claiming that the so-called European migrant crisis has come to an end, the critical scenarios regarding asylum seekers and refugees are far from being over. On one hand, the test posed by the refugee crisis has revealed the frailty of the EU’s values. Specially in those countries where populist nationalism is on the rise, promoting xenophobic attitudes. On the other, asylum seekers and refugees are facing, in their daily lives, even bigger challenges than those encountered during their journey, namely, integration. Similarly to Crusoe’s experience on the Island of Despair, these subjects, living in a strange land, often feel adrift, in a cognitive labyrinth where their “thinking as usual” (Schütz, 1944) is constantly on trial. Additionally, the inefficiency of organizations in providing support, has showed the limitations of highly bureaucratized systems in responding to the demands imposed by typical post-modern phenomena. Drawing from the results of 14 semi-structured interviews to asylum seekers and refugees hosted in Lisbon, this paper will focus on experiences of integration in Portuguese society and highlight unexpected gaps between agency and structural factors that determine the subjects’ autonomy. First results show that early access to language training and cultural orientation can be decisive for a successful participation in society. In fact, these subjects are the embodiment of Wittgenstein’s aphorism: “The limits of my language define the limits of my world”. This study is part of a greater body of research within the framework of the Pre and Post Arrival Schemes project, backed by the European Union’s AMIF, which objective is to develop improved processes of welcoming and first integration.